Social Consequences of Vehicle Exhaust: A Case Study in Poltava, Ukraine - Stepova, Olena; Hanoshenko, Olena; Serha, Tetyana; Yesina, Natalia; Strelnikova, Olena (Ecological Questions, 2021)
Intensive urbanization processes, an increase in the number of urban population and transport have led to an increase in the technogenic load on the environment, in particular on the atmospheric air. Among a significant number of sources of environmental pollution, roads and vehicles pose a significant threat. Motor vehicles cause irreparable harm to human health and the environment. Regular assessment of the quality of atmospheric air in residential areas of cities with heavy traffic to establish the level of potential risk to public health is an urgent task. The study purpose is the social consequences of transport emissions; determination of the anthropogenic load on the air and of the indicator of public health risk from the vehicle exhaust impact. The study was carried out on the example of the residential and the most loaded transport area of Poltava (Ukraine). The study demonstrates that the overwhelming majority of the urban population lives in areas where health risk indicators exceed permissible norms. Since the elderly, children and students are most often present on the street and near houses, they are at the greatest risk. The same applies to vehicle drivers who are often idle in "traffic jams". In turn, such high levels of air pollution pose even greater risks to public health, in particular to the development of respiratory diseases. In the study of the peculiarities of Ukrainian legislation in this area, it was established that the mechanism for collecting information about the quality of the environment, however, there is no requirement to inform the population about it.